Spinal malformations in a naturally isolated Neotropical fish population - Kerniske, Franciele Fernanda; Pena Castro, Jonathan; De la Ossa-Guerra, Luz Elena; Mayer, Bruna Angelina; Abilhoa, Vinícius; de Paiva Affonso, Igor; Ferreira Artoni, Roberto (PeerJ, 2021)
Fish populations that reside in completely isolated freshwater ecosystems are rare worldwide. The Vila Velha State Park (VVSP), located in southern Brazil, is recognized for its arenitic formations called sinkholes (furnas), which are completely isolated. Fish populations within, such as those of Psalidodon aff. fasciatus, often develop vertebral malformations due to this isolation from other conspecifics and other species. In this study, we analyzed geometric morphology in digital radiographs to identify congenital deformations of Psalidodon aff. fasciatus in Furna 2 of VVSP. We found many fish with spinal deformities, including wide variation in the number of caudal vertebrae and corporal deformations related to a flattened body and spinal curvature. Females were more affected than males. We also demonstrated that these deformations reflect inbreeding and an absence of gene flow in the population. In conclusion, isolated populations such as fish species in furnas are potential models for evo-devo research.
Keywords: Inbreeding; Spinal; Ontogenetic development; Gene flow